Genetic diversity of scorpions in Thien Duong and Tien Son caves base on mitochondrial COI gene analysis - Duong, Van Tang; Tran, Thi Viet Thanh; Nguyen, Van Mien; Phan, Thuy Vi; Tran, Thi Hang; Pham, Dinh Sac (Vietnam Journal of Biotechnology, 2025)
The mitochondrial cytochrome c oxidase subunit I (COI) genes of scorpions Vietbocap from the Thien Duong and Tien Son caves were sequenced and compared to assess the genetic diversity of populations. Phylogenetic trees and evolutionary maps were constructed to reveal the genetic affinities among the populations. A total of 32 polymorphic sites were identified in the 628-bp sequence of the mtDNA COI gene following sequence correction. The polymorphic loci were more than 10, the haplotype diversity was > 0.5, and the nucleotide diversity (Pi) was > 0.005. A total of five haplotypes were detected based on nucleotide variation among sequences. Scorpions in both Thien Duong and Tien Son caves were divided into three groups with significant genetic differences. The group in Tien Son cave exhibited clear distinctions when compared to the two groups in Thien Duong cave, with genetic distances of 4.33% and 4.64%, respectively. The two groups in Thien Duong cave were less differentiated, with a genetic distance of 0.68%. These results provide important genetic information for taxonomic study and offer a scientific basis for the existence of more than one species of scorpion within the populations at Thien Duong and Tien Son caves.